2010
DOI: 10.1681/asn.2010010127
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Regulation of Planar Cell Polarity in Polycystic Kidney Disease

Abstract: Mutations in PKD1, which encodes polycystin-1 (PC1), contribute to Ͼ85% of cases of autosomal dominant polycystic kidney disease (ADPKD). The planar cell polarity (PCP) pathway is necessary for the oriented cell division and convergent extension that establishes and maintains the structure of kidney tubules, but the role of this pathway in the pathophysiology of ADPKD is incompletely understood. Here, we show that inactivation of Pkd1 in postnatal developing mouse kidneys leads to a defect in oriented cell div… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
103
1
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(113 citation statements)
references
References 47 publications
(70 reference statements)
4
103
1
5
Order By: Relevance
“…27 In controls, 83% of dividing collecting duct cells had mitotic angles less than 30°, nearly parallel to the tubular longitudinal axis, whereas in mutants 50% of the non-dilated dividing collecting duct cells had mitotic angles greater than 30°(P,0.001) (Figure 8). There were no differences in proliferation in nondilated mutant collecting ducts versus controls (4%61.9% versus 4%62.5%, P=0.6), as measured by phospho-histone H3-positive cells over total cells.…”
Section: Fgfr2mentioning
confidence: 95%
“…27 In controls, 83% of dividing collecting duct cells had mitotic angles less than 30°, nearly parallel to the tubular longitudinal axis, whereas in mutants 50% of the non-dilated dividing collecting duct cells had mitotic angles greater than 30°(P,0.001) (Figure 8). There were no differences in proliferation in nondilated mutant collecting ducts versus controls (4%61.9% versus 4%62.5%, P=0.6), as measured by phospho-histone H3-positive cells over total cells.…”
Section: Fgfr2mentioning
confidence: 95%
“…Insights into possible human polycystin networks and downstream effector pathways were acquired from global and candidate approaches on human ADPKD kidneys and cell lines. These studies reported activation of developmental pathways including Wnt, Sonic Hedgehog, Notch, Hippo, bone morphogenic protein/transforming growth factor-β (BMP/TGFβ), ERK and transforming growth factor-α (TGFα) signaling (69,70,(73)(74)(75) that are known to regulate the c-Myc early growth response gene (6)(7)(8)(9). Studies from human ADPKD tissues pointed to one or several signaling pathways that converge on c-Myc as a key "cystogenic" factor.…”
Section: Upregulation Of C-myc In Human Adpkdmentioning
confidence: 99%
“…Notably, overexpression of Pkd2 in transgenic mice leads to increased c-Myc levels in kidneys with cystic anomalies (107,108). Molecular PC1 dysregulation identified stimulation of effectors from the Wnt, Hippo, Sonic Hedgehog, Notch, ERK and BMP/TGFβ cascades as uncovered by global profiling and candidate approach analyses (74,75,96,109). Remarkably, the signalling pathways activated in the orthologous mouse models virtually mimic those identified in human ADPKD studies, some of which are also deregulated in non-orthologous mouse models and result in c-Myc upregulation.…”
Section: Orthologous Pkd Mouse Models Co-associate With C-myc Overexpmentioning
confidence: 99%
“…[1][2][3] Although once considered a vestigial structure, the recent association of ciliary dysfunction with a host of genetic disorders known collectively as ciliopathies 2 has highlighted an array for roles for this organelle critical for both development and homeostasis. In the kidney, dysfunction of primary cilium results in a variety of ciliopathies 4 and modulates cystogenesis [5][6][7][8] and planar cell polarity (PCP). 6,9,10 An emerging class of functions involves signaling receptors and/or effectors delivered to the ciliary axoneme by specialized transport machinery and sequestered to regulate morphogenetic signaling pathways.…”
mentioning
confidence: 99%
“…In the kidney, dysfunction of primary cilium results in a variety of ciliopathies 4 and modulates cystogenesis [5][6][7][8] and planar cell polarity (PCP). 6,9,10 An emerging class of functions involves signaling receptors and/or effectors delivered to the ciliary axoneme by specialized transport machinery and sequestered to regulate morphogenetic signaling pathways. There are currently at least seven signaling cascades linked to a functional cilium, defects in which can be associated causally with some phenotypic aspects of ciliopathies.…”
mentioning
confidence: 99%